Does IFRS Impact Earnings Management of the JSE Firms - Adedeji Daniel Gbadebo (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: The paper considers how IFRS impacts discretionary accruals under the assumption that managers do not exercise discretion over revenue when involve in earnings management. The paper verifies whether the change in earnings management is due to time variation and should not be attributed the implementation of IFRS.Method: The paper employs random effects regression to examine the relationship between Jones model’ based discretionary accruals and IFRS-adoption, alongside other time-varying firm’s specific covariates including financial leverage, cash flow from operations, asset returns, equity returns, firms’ growth, firms’ size, and boot to market value.Findings: The paper finds that the estimate for the IFRS dummy was negative and significant, an indication that IFRS causes significant reduction in the discretionary accruals. Since earnings management is reduced after the adoption, this implies that IFRS has positive effects in practices. The paper further finds that earnings management is not purely time-driven and that it is robust to some specific covariates such as firm size, growth, and leverage.Novelty: The paper is novel because findings have importance for regulations, firms’ operations and future investigations. The evidence provides guidance to auditors in financial reporting, policy makers during policy formulation, investors in making informed decisions and regulators in their enforcement processes for the capital market.